ENTREPRENEURIAL COMPETENCIES OF ENGINEERING STUDENT AS A FACTOR OF SUCCESSFUL PROFESSIONAL CAREER - F. T. SHAGEEVA; M. F. GALIKHANOV; G. R. STREKALOVA (Moscow Polytechnic University, 2018)
State-of-the-art science and industry have changed professional activities of an engineer, e.g. he or she has to conduct entrepreneurial activity. One of the trends in university development is tending to University 3.0 (Education, Science, Entrepreneurship). It determines inescapable changes in future engineer education. Demand in such education programs is obvious; they would combine technical aspect of an idea with its commercial implementation. Synergetic effect appears only when engineer's talent meets manager's talent. That's why development of students' entrepreneurial competencies is set to become one of the learning objectives in engineering university. The paper describes an experience of the entrepreneurial competencies development in the context of research university.